(untitled) (Web of Teachers: Inderscience Research, 2025)
Objective:This article explores the integration of functional literacy and logical reasoning strategies into secondary chemistry education. The study aims to determine how modern pedagogical methods can enhance students’ ability to apply chemical knowledge to real-world problems and prepare them for international assessment frameworks. Method:The research employed a qualitative methodology based on cognitive pedagogy and constructivist learning theory. It utilized theoretical analysis, classroom-based experimentation, and diagnostic assessments. Interactive teaching tools such as graphic organizers, heuristic techniques, laboratory experiments, and Bloom’s taxonomy-based test formats were implemented to evaluate student progress. Results:Findings reveal that the application of functional literacy techniques significantly improves students’ analytical skills, practical competence in laboratory tasks, and understanding of both open and closed test formats. Students demonstrated increased motivation, more accurate use of chemical concepts in practical contexts, and enhanced capacity for independent learning and scientific inquiry. Novelty:Unlike previous studies that focus solely on subject knowledge acquisition, this research emphasizes the integration of meta-subject competencies—such as logical reasoning and reading literacy—within chemistry education. It offers a holistic framework for cultivating students’ intellectual engagement and international readiness through functional, interactive pedagogy.